Struktur, Kategori, dan Fungsi Sosial Pertanyaan Tradisional (Riddles) Masyarakat Nagari Tanjung Barulak Kecamatan Tanjung Emas Kabupaten Tanah Datar - Mutya Zulfayenis; Zulfadhli Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2022)
This research belongs to the type of qualitative research with descriptive method, which aims to describe (1) the traditional question structure (riddles) of the people of Nagari Tanjung Barulak, Tanjung Emas District, Tanah Datar Regency, (2) the category of traditional questions (riddles) of the people of Nagari Tanjung Barulak, Tanjung District. Emas District of Tanah Datar, and (3) the social function of traditional questions (riddles) for the people of Nagari Tanjung Barulak, Tanjung Emas District, Tanah Datar Regency. The data collection process was carried out in two stages, namely recording traditional questions (riddles) and collecting data about the storytelling environment. Meanwhile, the data analysis section was carried out using four stages, namely (1) the data transcription stage, (2) the data classification stage, (3) the discussion and conclusion stage of the results, and (4) the reporting stage. At the reporting stage, the research results can be described as follows: (1) the traditional question structure (riddles) of the Nagari Tanjung Barulak community, Tanjung Emas District, Tanah Datar Regency consists of: (a) conflicting traditional questions (riddles), and (b) traditional questions (riddles) which are not contradictory. (2) categories of traditional questions (riddles) for the people of Nagari Tanjung Barulak, Tanjung Emas District, Tanah Datar Regency, consisting of: (a) resemblance to humans, (b) resemblance to animals, (c) similarity to plants, (d) similarity to inanimate objects, and (e) similarity to color. (3) the social functions of traditional questions (riddles) of the people of Nagari Tanjung Barulak, Tanjung Emas District, Tanah Datar Regency are grouped into two parts, namely: (a) testing the intelligence of others, and (2) entertainment.